2014
DOI: 10.1128/iai.02480-14
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Mutation of the Sensor Kinase GraS in Staphylococcus aureus Alters the Adaptive Response to Distinct Cationic Antimicrobial Peptides

Abstract: The Staphylococcus aureus two-component regulatory system, GraRS, is involved in resistance to killing by distinct host defense cationic antimicrobial peptides (HD-CAPs). It is believed to regulate downstream target genes such as mprF and dltABCD to modify the S. aureus surface charge. However, the detailed mechanism(s) by which the histidine kinase, GraS, senses specific HD-CAPs is not well defined. Here, we studied a well-characterized clinical methicillin-resistant S. aureus (MRSA) strain (MW2), its isogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 48 publications
3
60
1
Order By: Relevance
“…The most common mprF SNP observed in the study strains resulted in either an L826F or T345A/K/I substitution, constituting 27% and 18%, respectively. These SNPs are well-known mprF hot spot mutations linked to DAP resistance (see below) (14,19,22,23,25,38,41,42). Although the C8, C23, and C35 strains had DAP MICs of 3 to 4 mg/liter, the mprF ORFs and promoter sequences of these strains were identical to those of the each respective DAP s parental strain (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The most common mprF SNP observed in the study strains resulted in either an L826F or T345A/K/I substitution, constituting 27% and 18%, respectively. These SNPs are well-known mprF hot spot mutations linked to DAP resistance (see below) (14,19,22,23,25,38,41,42). Although the C8, C23, and C35 strains had DAP MICs of 3 to 4 mg/liter, the mprF ORFs and promoter sequences of these strains were identical to those of the each respective DAP s parental strain (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study shed light on the molecular mechanism used by GraS to sense certain CAMPs with more sensitivity than others. 106 Interestingly, the GraSR locus encodes a third subunit (GraX) that is predicted to form a part of the sensing mechanism. 102-104 Together with previous observations showing that expression of mprF and dltABCD is dependent on a functional VraFG, new studies have shown that GraX is the central component of a “5-component system” for sensing of CAMPs (Fig.…”
Section: Regulation Of Pg Aminoacylationmentioning
confidence: 99%
“…MW2 (USA400) is a prototypic and well-characterized clinical isolate with a known genome that has been demonstrated to be virulent in multiple animal models. graS mutant strains were generated by in-frame deletion of target genes by allelic replacement using the temperature-sensitive plasmid pMAD as previously detailed (7). Organisms were cultured in brain heart infusion broth (BHI) (Becton Dickinson) at 37°C with shaking overnight (ϳ16 h), subcultured under identical conditions for 3 h to logarithmic phase, harvested by centrifugation, washed, and resuspended to the appropriate CFU (culture confirmed) by spectrophotometry for each specific assay.…”
Section: Methodsmentioning
confidence: 99%
“…RP-1 was synthesized, purified, and authenticated as previously detailed (9). Each study peptide has demonstrated in vitro antimicrobial activity against S. aureus (3,7,8,10). sEL sensor domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation